Determination of the Factors Affecting High School Students’ Preferences of and Satisfaction with Choosing Biology as an Elective Course - Nazihan Ursavas; Adem Kesimal (Universitas Pendidikan Indonesia, 2020)
School subjects are divided into two as compulsory and elective courses. Compulsory courses are the basic courses that students must take in order to graduate, while elective courses are the ones that students are at liberty to take. In Turkey Biology course was taught as compulsory under the name of common courses in all levels of high schools. With the new amendment Biology is started to taught as elective under the name of “Advanced Biology” in Anatolian High Schools and “Biology Applications” in Science High Schools at grade eleven and twelve. This new development has brought to mind what the reasons are for choosing and not choosing biology. In order to reveal this aim 135 volunteered students were questioned from two different schools located in the northeastern Turkey. An open-ended question test was used for data collection. The information received from the students was subjected to content analysis. The factors that lead students to choose biology or not to choose biology are identified as future orientedness on both categories. Students want to change their decisions because of course related and exam-orientation reasons. Future studies can utilize larger samples, in terms of gender differences and in the contexts of other elective courses.